Pengaruh Latihan Imagery terhadap Peningkatan Kepercayaan Diri dan Konsentrasi Siswa Ekstrakurikuler Bola Voli di SMPN 2 Gunungsari - Sukartidana, I Nyoman; Syahroni, Mohammad (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2025)
This study aims to examine the effect of imagery training on improving self-confidence and concentration of volleyball extracurricular students at SMPN 2 Gunungsari. A quasi-experimental method with a matching only design was employed, involving 18 students divided into experimental and control groups. The experimental group received imagery training for two weeks with a frequency of four sessions per week. Data were collected using the State Sport Confidence Inventory (SSCI) to measure self-confidence and the Grid Concentration Exercise Test to assess concentration. The paired sample t-test results showed a significant effect of imagery training on self-confidence and concentration with a significance value of 0.000 (p < 0.05). The study concludes that imagery training effectively improves students' self-confidence and concentration. It is recommended that coaches and physical education teachers integrate imagery training regularly into their training programs and combine it with other mental techniques for optimal results.